The differences response of massage types with variation massage pressure on running speed in POPDA Sleman athletics - Rini, Riza Galih Mustika; Purnomo, Eddy (Program Studi Ilmu Keolahragaan Program Pascasarjana Universitas Negeri Yogyakarta, 2021)
This study aims to improve the athlete's performance from the physiological aspect by knowing the differences in the response of sport massage and swedish massage with variations in pressure (light, medium, and heavy) on the hind limbs a 30 m running speed taken four times. This research is a quasi-experimental design, with the research subjects of POPDA Sleman athletic athletes with sample of 20 people. The sample was divided by matching pairs with the aim of both groups getting a balanced power. The treatments used are sports massage with movement manipulation (effleurage, tapotement, shaking/vibration) and swedish massage with movement manipulation (drainage, compression, tapotement, shaking/vibration) with pressure variation. The results showed that there were differences in the effect/good response of the type of sports massage treatment (group x) with moderate pressure. This is evidenced by the results of an increase in record time by an average of 0.36 seconds. Treatment of light pressure increased record time by an average of 0.28 seconds. Heavy pressure treatment increased record time by an average of 0.04 seconds. There is a difference in the effect/unfavorable response of the type of swedih massage treatment (group y) with all types of pressure, because it provides a decreased response time from pretest to posttest. It is proven by the decrease in the average time of 0.16 seconds on the light pressure treatment, the decrease in the average time of 0.24 seconds on the medium pressure treatment, and a decrease of 0.34 seconds on the heavy pressure treatment.